2013
DOI: 10.1038/nature12745
|View full text |Cite|
|
Sign up to set email alerts
|

Derivation of novel human ground state naive pluripotent stem cells

Abstract: Mouse embryonic stem (ES) cells are isolated from the inner cell mass of blastocysts, and can be preserved in vitro in a naive inner-cell-mass-like configuration by providing exogenous stimulation with leukaemia inhibitory factor (LIF) and small molecule inhibition of ERK1/ERK2 and GSK3β signalling (termed 2i/LIF conditions). Hallmarks of naive pluripotency include driving Oct4 (also known as Pou5f1) transcription by its distal enhancer, retaining a pre-inactivation X chromosome state, and global reduction in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

52
1,137
8
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 948 publications
(1,227 citation statements)
references
References 29 publications
52
1,137
8
5
Order By: Relevance
“…Previous studies have also suggested that human primed iPSCs and mouse EpiSCs can be converted to the naïve ground state via chemical manipulation or the overexpression of specific transcription factors [12][13][14][15][16][17]. Recently, several groups have further modified culture conditions to maintain human ESCs or iPSCs in the naïve ground state [12,13,15,18]. In particular, the 5i/L/FA system, developed by Jaenisch's group, contains a combination of inhibitors and growth factors sufficient for the induction and maintenance of the naïve ground state [15].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have also suggested that human primed iPSCs and mouse EpiSCs can be converted to the naïve ground state via chemical manipulation or the overexpression of specific transcription factors [12][13][14][15][16][17]. Recently, several groups have further modified culture conditions to maintain human ESCs or iPSCs in the naïve ground state [12,13,15,18]. In particular, the 5i/L/FA system, developed by Jaenisch's group, contains a combination of inhibitors and growth factors sufficient for the induction and maintenance of the naïve ground state [15].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the HES2 line, DS is broadly applicable for aggregation control across different cell lines and culture conditions. We cultured the H9 PSC line in a medium containing DS in both conventional PSC culture conditions and conditions supporting a “naïve” pluripotent state (Gafni et al, 2013) and found that the DS is able to control H9 PSC aggregation in both pluripotent states (Supporting Information Figure S1h).…”
Section: Resultsmentioning
confidence: 99%
“…For example, since human ESCs bear numerous similarities to EpiSCs [5,6], our model predicts that ectopic Cdx2 would not induce expression of TSC-like cell genes in human ESCs in the conditions we tested here. Recently, totipotent or naïve pluripotent stem cell lines have been derived from both humans and mice [56][57][58][59][60]. In several cases, these cell lines have been shown to contribute to extraembryonic lineages in chimeras.…”
Section: Figmentioning
confidence: 99%